„Dobra reprodukcja obrazów”. „Dzieło” Émile’a Zoli w przekładach Aleksandry Callierowej i Hanny Szumańskiej-Grossowej - Jarmuszkiewicz, Anna (Poznańskie Studia Polonistyczne. Seria Literacka, 2023)
The article describes a series of Polish translations of Émile Zola’s 1886 novel L’OEuvre. The translations made by Aleksandra Callierowa (1886) and by Hanna Szumańska-Grossowa (1959) were created at completely different points in history, which significantly affects both the poetics of the translations and their reception. Callierowa’s translation was contemporary to the original, it conveyed the need to quickly keep up with the fashion prevailing in literature. Szumańska-Grossowa’s work, in turn, accentuates the fact that Zola already belonged to the canon of European literature and that he deserved – in accordance with the ideological assumptions of the then communist authorities – to be read bya mass reader.